1992
DOI: 10.1111/j.1559-3584.1992.tb02246.x
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Navy Composite Developments for Thermal Management

Abstract: This paper reviews: (1) Navy sponsorship of pitch graphite fiber development, and (2) assesses the impact of the high thermal conductivity fibers on future Navy applications. Navy exploratory development programs (6.2) have revealed potential applications in advanced systems for graphite fiber reinforced composites: (1) electronic packaging, (2) satellite radiators, and (3) elevated temperature applications such as missiles. Thermal management in these applications can be improved through the development and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…They can be simply fabricated at a relatively low cost and easily machined into finished products, and thus are extensively used in thermal management fields [1][2][3][4]13]. For instance, vapor grown carbon fiber-reinforced epoxy matrix composite hot-pressed at 150 °C exhibits a thermal conductivity as high as 695 W/m K in the direction parallel to the oriented fibers with a density of 1.5 g/cm 3 , and it has an electrically insulating surface unlike carbon fiber-reinforced carbon or metal matrix composites [14].…”
Section: Introductionmentioning
confidence: 99%
“…They can be simply fabricated at a relatively low cost and easily machined into finished products, and thus are extensively used in thermal management fields [1][2][3][4]13]. For instance, vapor grown carbon fiber-reinforced epoxy matrix composite hot-pressed at 150 °C exhibits a thermal conductivity as high as 695 W/m K in the direction parallel to the oriented fibers with a density of 1.5 g/cm 3 , and it has an electrically insulating surface unlike carbon fiber-reinforced carbon or metal matrix composites [14].…”
Section: Introductionmentioning
confidence: 99%
“…Indicating that the number of graphite flakes along the perpendicular direction of the plate samples increases. It has been reported that the thermal conductivity along the graphite layers is much larger than that of cross layers [34,35]. We could conclude that the Sn has a synergistic effect with graphite on the improvement of the thermal conductivity of PA6.…”
Section: Thermal Conductivities Of the Compositesmentioning
confidence: 49%
“…[4,9] The carbon content of the PAN system is 93-98 wt %, with less than 0.05 % of water adsorbed; however, there are several GP-grade CFs that are relatively hydrophilic. [14] However, since both weight loss and a decrease in strength are observed above 350 8C, due to oxidation, CFs are not suitable for high-temperature processing. The present CFs comprise phases containing elements other than carbon.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
“…Because CFs do not show any significant expansion and/or shrinkage in response to temperature changes, they are suitable for use in outer space where the temperature difference between day and night reaches 300 8C, in particular, as a material for satellites. [14] However, since both weight loss and a decrease in strength are observed above 350 8C, due to oxidation, CFs are not suitable for high-temperature processing. Furthermore, when CFs are used as fillers for ceramics they are likely to react with oxides during the calcination process, which leads to deterioration.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%